Arthroscopic Reverse Bankart Surgical Repair - Robert S. Dean MD; Anirudh K. Gowd MD; Carson D. Bunker; Edward C. Beck MD, MPH; Eric J. Dennis MD; Brian R. Waterman MD (SAGE Publishing, 2021)
Background: Posterior glenoid labrum lesions occur in only 2% to 10% of all cases of shoulder instability, yet these injuries may cause significant shoulder dysfunction in an athletic population. Moreover, these injuries frequently require surgical intervention and present a unique surgical challenge. Indications: Indications for arthroscopic posterior labral repair include symptomatic posterior labral tears identified on magnetic resonance imaging with or without contrast, that failed nonsurgical management (ie, lifestyle modification, nonsteroidal anti-inflammatory drug, and physical therapy). Patients may present with a positive posterior load and shift or positive posterior apprehension test. Technique Description: With the patient in the lateral decubitus position, use a standard posterior superior portal, an ancillary anterior superior portal, a posterior-inferior, and the portal of Wilmington. After portal placement and diagnostic arthroscopy, the torn labrum is debrided. The torn portion of the posterior labrum is then mobilized from approximately the 6 o'clock to 10 o'clock positions, and a curette and shaver are used to produce a bleeding margin for fixation. Two double-loaded 2.4-mm suture anchors are placed, passed, and tied; one at the 6:30 o'clock position and the other at the 8 o'clock position. A cinch stich configuration using a 2.9-mm pushlock anchor can be used at the 10 o'clock position. A polydioxanone suture is used to assist with capsular plication and to close the posterior portal. Results: The literature suggests that 90% to 94% of patients are able to return to their desired sport with 5% to 10% reporting recurrent instability by 2 years after operation. Two out of 3 patients report no limitations at 2 years. Discussion/Conclusion: Arthroscopic repair of posterior labral tears with suture anchors can be an effective surgical option for patients with reverse Bankart lesions. Using advanced imaging to identify concomitant pathologies, meticulous surgical technique, direct visualization of the anatomy and anchor placement, and a dedicated rehabilitation program, greater than 90% of patients can expect to return to sport.